Resistance training and skeletal muscle protein metabolism in eumenorrheic females: Implications for researchers and practitioners - Knowles, O. E.; Aisbett, B.; Main, L. C.; Drinkwater, E. J.; Orellana, L.; Lamon, S. (Sports Medicine, 2019)
Resistance training is essential for health and performance and confers many benefits such as increasing skeletal muscle mass, increasing strength and power output, and improving metabolic health. Resistance training is a major component of the physical activity guidelines, yet research in female populations is limited. Recent increases in the promotion of, and the participation by, females in sport and exercise, highlight the need for an increase in understanding of evidence-based best practice exercise prescription for females. The aim of this review is to provide an overview of the current research regarding resistance training performance and skeletal muscle adaptation in females, with a focus on the hormonal variables that may influence resistance training outcomes. Findings suggest that the menstrual cycle phase may impact strength, but not skeletal muscle protein metabolism. In comparison, oral contraception use in females may reduce skeletal muscle protein synthesis, but not strength outcomes, when compared to non-users. Future research should investigate the role of resistance training in the maintenance of skeletal muscle protein metabolism during pregnancy, menopause and in athletes experiencing relative energy deficiency in sport. The review concludes with recommendations for researchers to assist them in the inclusion of female participants in resistance training research specifically, with commentary on the most appropriate methods of controlling for, or understanding the implications of, hormonal fluctuations. For practitioners, the current evidence suggests possible resistance training practices that could optimise performance outcomes in females, although further research is warranted.